2017
DOI: 10.30958/ajss.4-2-4
|View full text |Cite
|
Sign up to set email alerts
|

The Big 12: The Most Important Character Strengths for Military Officers

Abstract: The Norwegian Military Academy's main role is to educate future military leaders for the Norwegian Army. After graduating from the Norwegian Military Academy, these leaders will most likely have to deal with a great deal of responsibility and to cope with challenging and difficult situations. Leadership in these situations will demand a high degree of both intellect and character. Systematic research on the specific character strengths that are crucial to possess for military officers to succeed as military le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
11
0
1
Order By: Relevance
“…In a second study, applicants with teamwork as a core strength were 2.6 times more likely to pass the selection process [7]. Finally, Boe and Bang found that leadership, persistence, bravery, teamwork, fairness, social intelligence, love of learning, perspective, self-regulation, and creativity were identified as particularly relevant and important for succeeding as an officer in the Norwegian Army [8].…”
Section: Introductionmentioning
confidence: 93%
“…In a second study, applicants with teamwork as a core strength were 2.6 times more likely to pass the selection process [7]. Finally, Boe and Bang found that leadership, persistence, bravery, teamwork, fairness, social intelligence, love of learning, perspective, self-regulation, and creativity were identified as particularly relevant and important for succeeding as an officer in the Norwegian Army [8].…”
Section: Introductionmentioning
confidence: 93%
“…A list of character strengths and competencies was given. The participants were then requested to judge each character's strength and competency separately based on their subjective perception of the importance (BOE, et al, 2017) for foreign language professional intercourse of officers. These were in ranked divided into several blocks: management skills, intellectual, emotional and motivational, behavioral, spiritual and moral, communicative qualities and skills.…”
Section: Students' (Cadets') Perceptions On Importance Of Readiness For Foreign Languagementioning
confidence: 99%
“…Crucially these values reflect the key components of character, Wisdom, Courage, Humanity, Justice, Temperance and Transcendence (Devettere, 2002, Ros-Morente, 2018. Numerous authors (Matthews et al, 2006, Boe andBang, 2017) have drawn comparisons between these values and the mental and emotional strengths required of an army leader such as self-discipline, judgement, positive attitude and creative thinking (Table 3). It can therefore be asserted that the DF values are typical of character we should seek to develop in our leaders.…”
Section: Integritymentioning
confidence: 99%